A Situationer on the Indigenous Peoples of Negros Oriental - Soluta, Andrea G.; Manginsay, Glynis Wilfa V.; Pioquinto, Cere (Silliman Journal, 2023)
The data in this paper have been culled from the results of the baseline survey using a set of questionnaires and conducted through structured interviews during the period July to November 1996 by the Silliman University-DENR Task Force on Ancestral Domains, We wish to thank the three indigenous cultural communities, through their respective tribal associations, for permission to publish these data.